The educational response to Covid-19 across two countries: a critical examination of initial digital pedagogy adoption - Greenhow, Christine; Lewin, Cathy; Staudt Willet, K. Bret (Technology, pedagogy and education)
In spring 2020, K-12 schools adopted remote learning amidst the Covid-19 pandemic. Using activity theory, the authors examine the educational response to this global health crisis in the United States and the United Kingdom. Data are drawn from key news media publications in each country between 1 February and 31 May 2020. The authors critically examine the tensions and contradictions within and between interrelated systems (schooling, educational policy, home learning). They consider how remote digital pedagogy was perceived and enacted by different stakeholders: teachers, parents, policymakers. Tensions arose between digital pedagogy, system rules and teachers' digital skills, leading to different experiences for students. The division of labour shifted; parental responsibility for managing children's learning increased. Digital equity issues prevailed in both countries (technology access, social support), disadvantaging students from low-income families. National educational policy system responses were more coordinated in the UK than in the US.